Gestão da QOS em arquiteturas de grades computacionais orientadas a serviços - Cedro, Daniela Medeiros (2010)
The increasing deployment of services on the Internet is augmenting the demand for processing resources on the server side encouraging the use of Clusters of Computers and Grid Computing. At the same time, the engineering software brings new paradigms such as Service Orientation, which impose new challenges to be addressed by service providers. The convergence of these factors led Architectures for Service Oriented Grid Computing. This work presents an architecture proposed for service oriented grid computing, called G-DSAC (Grid - DiffServ Admission Control), which deals with aspects related to QoS (Quality of Service) and service differentiation. The G-DSAC architecture is an extension of WS-DSAC architecture (Web Servers - AdmissionControl DiffServ). This extension includes design of a Service Oriented Grid Computing Architecture which is able to ensure SLAs (Service Level Agreements) established with consumers using effectively the resources available in the grid. The solution also provides service differentiation in relation to response times offered to customers, end users and service consumers. The proposed new architecture introduces a block of functionality in a service oriented grid computing platform composited by Multclusters. This block allows publishing and localization of services, authentication and classification of requests and scheduling of those within the grid according to the service class they belong. It was also implemented a prototype that allowed the realization of experiments in a testing platform to evaluate the solution's ability to achieve the objectives proposed by the new architecture.